AKUPRESUR SP6 TERHADAP NYERI PERSALINAN KALA I FASE AKTIF - Ariesty, Ghina Ayu; Mariza, Ana; Evrianasari, Nita; Isnaini, Nurul (MIDWIFERY JOURNAL, 2021)
Labor pain begins to arise in stage I, which comes from uterine contractions and cervical dilation, labor pain can cause complications of labor, one of which is prolonged labor. Prolonged labor is the most reported complication (41%). One of the techniques for reducing labor pain is acupressure SP6. The research objective was to determine the effect of SP6 acupressure on the intensity of active phase I labor pain at Airan Raya Hospital, South Lampung in 2020. This type of quantitative research uses a quasi-experimental approach and pre-post test design. The time of the study was conducted from April to July 2020. The population in this study were all stage I inpartum patients at Airan Raya Hospital, South Lampung in 2020, a sample of 28 people, using purposive sampling technique. The independent variable was Acupressure SP6, the dependent variable was labor pain. Data collection using the VAS observation sheet, univariate and bivariate data analysis (t test). The results of the study the mean labor pain before being given the SP6 acupressure technique was 7.3 and after being given the SP6 acupressure technique was 5.47. There is an effect of the SP6 acupressure technique on active phase I labor pain at Airan Raya Lampung Selatan Hospital in 2020 (p-value 0.00 <0.05) with a decrease of 1.83. It is suggested for mothers to disseminate their experiences, especially the SP6 acupressure action which aims to reduce pain during labor, so that it can be information for other mothers who are about to give birth. For health workers, improve the skills of officers to perform acupressure techniques SP6. Keywords : SP6 acupressure, labor pain, Active phase I Labor Pain ABSTRAK Nyeri persalinan mulai timbul pada tahap kala I yang berasal dari kontraksi uterus dan dilatasi seriks, nyeri persalinan dapat menimbulkan komplikasi persalinan salah satunya adalah partus lama. Partus lama adalah komplikasi yang paling banyak dilaporkan (41%), salah satu tekhnik untuk pengurangan nyeri persalinan adalah denganakupresur SP6. Tujuan penelitian diketahui pengaruh akupresur SP6 terhadap intensitas nyeri persalinan kala I fase aktif di RS Airan Raya Lampung Selatan tahun 2020. Jenis penelitian kuantitatif dengan rancangan penelitian quasi eksperiment dengan pendekatan pre dan post test design. Waktu penelitian dilakukan dari bulan April – Juli 2020. Populasi dalam penelitian ini adalah semua pasien inpartu kala I di RS Airan Raya Lampung Selatan tahun 2020, sampel sebanyak 28 orang, tekhnik sampling dengan Purposive Sampling. variabel independen adalah Akupresur SP6, dependen nyeri persalinan. pengumpulan data dengan lembar observasi VAS, analisis data secara univariat dan bivariat (uji T). Hasil penelitian rata-rata nyeri persalinan sebelum diberikan teknik akupresur SP6 adalah 7,3 dan setelah diberikan teknik akupresur SP6 adalah 5,47. Ada pengaruh teknik akupresur SP6 terhadap nyeri persalinan kala I fase aktif di RS Airan Raya Lampung Selatan tahun 2020 (p–value0,00< 0,05) dengan penurunan 1,83. Disarankan bagi ibu untuk menyebarluaskan pengalaman yang didapat, khususnya tindakan  akupresur SP6  yang bertujuan untuk pengurangan nyeri selama persalinan berlangsung, sehingga dapat menjadi informasi bagi ibu yang akan bersalin lainnya. Bagi petugas kesehatan, agar meningkatkan keterampilan petugas untuk melakukan teknik akupresur SP6. Kata kunci  : Akupresur SP6, Nyeri Persalinan, Kala I Fase Aktif